Allogeneic Hematopoietic Cell Transplantation for Therapy-Related Myeloid Leukemia following Orthotopic Cardiac Transplantation. (30th March 2013) - Lin, Richard J.; Larson, Richard A.; van Besien, Koen; Rich, Elizabeth S.
Abstract : Therapy-related myeloid neoplasm (t-MN) is a subtype of acute myeloid leukemia with adverse cytogenetics and poor overall prognosis despite intensive induction chemotherapy and allogeneic hematopoietic cell transplantation (allo-HCT). It is increasingly recognized as a late complication of chronic immunosuppression in patients who have received solid organ transplantation. In this paper, we describe a case of t-MN following orthotopic cardiac transplantation and its treatment with allo-HCT. We discuss molecular and biological challenges and considerations in double solid organ and bone marrow transplantation and review similar cases at our institution. Our experience suggests general feasibility and safety of allo-HCT in patients who have received solid organ transplantation.